Worm infections of the digestive tract in Serama chickens which are kept in closed cages at Ricky's farm Cimanggu - Rachman, Muh Rifky; Siagian, Tetty Barunawati; Jasmine, Dennisa Maharani; Sinsinillah, Siti Zahidah (ARSHI Veterinary Letters, 2024)
Serama chickens are ornamental chickens often susceptible to gastrointestinal worm infections. This study aimed to identify the digestive tract worms infecting Serama chickens kept in closed cages. Five fecal samples from Serama chickens at Rifky's Farm in Cimanggu were used for the research. Stool examinations were conducted qualitatively using native and flotation methods and quantitatively with the McMaster method. The examination results revealed the presence of trichurid eggs, with a 60% infection rate and a light to heavy infection, indicated by an eggs per gram value of 133-1,800. The identified worm species was Capillaria sp., likely due to the closed and humid conditions of the cages, which favor the development of infective eggs and facilitate direct infection.